POLA KAJIAN HADIS AKADEMIK DI PERGURUAN TINGGI KEAGAMAAN ISLAM NEGERI (PTKIN) DI INDONESIA (Studi Skripsi Mahasiswa Tafsir Hadis UIN Raden Fatah Palembang, UIN Syarif Kasim Pekanbaru dan UIN Imam Bonjol Padang) - Adriansyah NZ (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2018)
The study of hadith at the Indonesian Islamic College (PTAI) has a pattern, variety and characteristics in accordance with their respective characteristics. The various types and forms of courses offered in the study of hadith indicate a continuous dynamic. The Department of Interpretation of the Hadith of Raden Fatah UIN in Palembang, UIN Syarif Kasim Pekanbaru and UIN Imam Bonjol Padang in the field of Hadith Science, took refuge, which has resulted in many alumni. Ideally their works are disseminated to the public in order to obtain positive impact on religious life. The reality is not the case, to this day no one has seriously searched through research. This research is important to know the pattern and typical study of academic hadith that develops on students of the interpretation of hadith, especially the study program of Hadith at UIN Raden Fatah Palembang, UIN Syarif Kasim Pekanbaru and UIN Imam Bonjol Padang and provide adequate contributions in the development of hadith studies in Indonesia. So far, the most dominant model of hadith study in thesis writing of the student of UIN Raden Fatah Palembang and UIN Imam Bonjol Padang is hadith fiqh. While UIN Syarif Kasim Pekanbaru is more inclined towards the criticism of hadith (naqd al-hadith). Theme of the thesis study most in demand by students of the Raden Fatah UIN Palembang and UIN Imam Bonjol is a matter of shari'a, in contrast to UIN Syarif Kasim Pekanbaru, it is more inclined to the theme of the traditions of worship. The methodology of the study of academic hadith studies used by students in conducting hadith research is textual, intertextual and contextual.